THE SEA FACTOR IN THE SPATIAL AND SOCIO-ECONOMIC DYNAMICS OF TODAY’S RUSSIA - Druzhinin, Alexander (Quaestiones Geographicae, 2019)
The World Ocean and, in particular, its resource potential have always had a dramatic effect on the progress and spatial organisation of humanity. Recently, the effect of the sea factor on the economy and the settlement system has increased amid globalisation, geoeconomic changes, increasing geopolitical turbulence, and the growing competition for resources. In this article, I attempt to assess the influence of the sea factor on the socioeconomic geography of the Russian Federation. A country with an extensive coastline and a vast inland area, Russia has territories that are very different in geographical terms. I pay special attention to the post-Soviet changes in the major components of the country’s maritime economy: seaports, fishing industry, offshore production, recreation, etc. Another focus is the assessment of these industries’ impact on the development of the coastal areas. I demonstrate the growing dependence between the maritime economy and the economic development of Russia’s inland regions. I identify the key natural geographic, foreign economy, settlement-related, and geopolitical factors of the coastalisation of the economy, infrastructure, and population, observed in Russia today. This process is taking place in the Baltic, Black, and Caspian Sea areas, as well as in the Arctic and Pacific regions of the country. I conclude that Russia’s integration into the system of multi-dimensional Eurasian partnerships (including the Belt and Road initiative) and the ‘turn to the East’ contribute to both the further ‘marinisation’ of Russian space and the differentiation of coastal zones by the level and rates of socio-economic development.